Discovery-Learning Based Handout Teaching Media Using Design-Thinking Model to Improve Students’ Learning Outcomes on Earth Structure Material - Rahmah Salamah Nur Azizah; Achmad Samsudin; Suparmo Suparmo (CV FOUNDAE, 2024)
This study aims to develop a discovery learning-based handout teaching media to improve student learning outcomes on earth structure material. The research method used was development research with Educational Design Research (EDR) design which refers to the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) model with a design thinking framework. The population of this study was 32 eighth-grade students in one of the junior high schools in Bandung, using a convenient sampling technique. One class was selected, which consisted of 16 male students and 16 femalestudents, all with an average age of 14. The class selection was based on the science teacher's recommendation. The research instrument was a validation sheet and student learning outcomes test. The data analysis technique used was the validity test of the teaching media and the effectiveness test of student learning outcomes. The results of this study indicated that the validation test data obtained a validity percentage of 93.57% in the highly valid criteria. The N-gain result of the learning effectiveness test was 0.56 in the medium category. The findings showed that using media effectively supports and improves student learning outcomes. This research makes a significant contribution to the field of education, providing clear and practical guidance for educators in creating more interesting and effective teaching media. In addition, this research also contributes to efforts to improve the quality of learning at the secondary education level, especially in the context of science learning in Indonesia.